Exploring conservation discourses in the Galapagos Islands: A case study of the Galapagos giant tortoises - Benitez-Capistros, Francisco (Ambio, 2016)
Conservation discourses change rapidly both at global and local scales. To be able to capture these shifts and the relationships between humans and nature, we focused on a local and iconic conservation case: the Galapagos giant tortoises (Chelonoidis spp.). We used the Q methodology to contextualize conservation for science and decision making and to explore the multidimensionality of the conservation concept in Galapagos. The results indicate four prevailing discourses: (1) Multi-actor governance; (2) giant tortoise and ecosystems conservation; (3) community governance; and (4) market and tourism centred. These findings allow us to identify foreseeable points of disagreement, as well as areas of consensus, and to discuss the implication of the findings to address socio-ecological conservation and sustainability challenges. This can help the different involved stakeholders (managers, scientists and local communities) to the design and apply contextualized conservation actions and policies to contribute to a better sustainable management of the archipelago. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13280-016-0774-9) contains supplementary material, which is available to authorized users.